Characteristic Flavor of Traditional Soup Made by Stewing Chinese Yellow‐Feather Chickens - Qi, Jun; Liu, Deng‐yong; Zhou, Guang‐hong; Xu, Xing‐lian (Journal of food science, 2017)
The traditional recipe for Chinese chicken soup creates a popular taste of particular umami and aroma. The present study investigated the effects of stewing time (1, 2, and 3 h) on the principal taste‐active and volatile compounds and the overall flavor profile of traditional Chinese chicken soup by measuring the contents of free amino acids (FAAs), 5′‐nucleotides, minerals and volatile compounds and by evaluating the taste and aroma profiles using an electronic nose, an electronic tongue and a human panel. Results showed that the major umami‐related compounds in the chicken soup were inosine 5′‐monophosphate (IMP) and chloride, both of which increased significantly (P < 0.05) during stewing. The taste active values (TAVs) of the equivalent umami concentration (EUC) increased from 4.08 to 9.93 (P < 0.05) after stewing for 3 h. Although the FAA and mineral contents increased significantly (P < 0.05), their TAVs were less than 1. The volatile compounds were mainly hexanal, heptanal, octanal, nonanal, (E)‐2‐nonanal, (E)‐2‐decenal, (E,E)‐2,4‐decadienal, 1‐hexanol, and 2‐pentyl furan. With the prolonged stewing time, the aldehydes first increased and then decreased significantly (P < 0.05), while 1‐hexanol and 2‐pentyl furan increased steadily (P < 0.05). The aroma scores of the chicken soup reached the maximum after stewing for 3 h. The discrepancy in overall flavor characteristics tended to stabilize after 2 h of stewing. In general, stewing time has a positive effect on improving the flavor profiles of chicken soup, especially within the first 2 h. Practical Application The information obtained not only provides insight into the changes in odor and taste of chicken soup during cooking but also provides guidelines that can be followed to improve the stewing process.